The future of inter-Arab relations - Fahmy, Nabil (Emirates lecture series, 2013)
When the dust of the last few years finally begins to settle, I believe that we will find an Arab World aware of these new realities and struggling to find common ground, even if it initially feels the discomfort of diversity. These are transformative and historic times, for we are redefining the identity and profile of the Arab World in the 21st century. As a result of this struggle, relations between Arab countries will ultimately be enhanced by life in a more open world, by better and more transparent governance that is accountable to the people, and by more inclusive and competitive political systems. These will not be simple choices between monarchies or republicsu2014both can succeed or fail. These changes will take time and come at a human and material cost, but they will ultimately render a clearer vision of what the rest of the world may look like in the coming two decades, as well as highlight the importance of new and adaptive foreign policies. Whether in terms of new emerging powers, an inevitable shift in the flow of energy and food markets, issues of local and global environmental degradation, or the development of new and more sophisticated technologies. As we navigate our course through these challenging times, the Arab World will witness serious change and evolving roles for different regional players. The future of the Arab World will not only be determined by the political transformations of the Arab Awakening, but also by globally occurring transformations. For a variety of historical, demographic, geographic, economic and political reasons, the countries that can particularly influence these changes will continue to be Algeria, Egypt, Iraq and Saudi Arabia. However, as our societies becomes more inclusive and more diversified, the role of every Arab state becomes even more important. Like the rest of the world, the Arab region will become more multipolaru2014a complicated but inevitable healthy transformation. Many only see darkness in the time ahead and I too must acknowledge the serious challenges before us. However, we must deal with todayu2019s reality and its challenges; this is not a choice but an imperative. Despite such challenges, I see concrete opportunities to weave a more real and globally relevant, but much-changed Arab World in the decade to come. Most important, we must fight the urge to drift further apart out of fear of change; for change has been continuous and will always be inevitable.